Community Watch Corps (CWCs) & The Fight Against Armed Bandits In Katsina State: An Assessment of Operational Methods - Muhammad Abdullahi Maigari; Ishaq Usman Karofi; Maikano Madaki (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
This study investigates the modus operandi adopted by the Community Watch Corps (CWCs) in combating insecurity across six high-risk Local Government Areas (LGAs) in Katsina Central Senatorial District, Nigeria. Using a mixed-methods research design, the study combines data from 385 survey respondents and 17 Key Informant Interviews (KIIs) involving religious leaders, traditional rulers, and CWCs personnel. Employing multistage cluster sampling for the quantitative strand and purposive sampling for the qualitative, the research uncovers how CWCs operationalise community policing through coordinated strategies such as routine patrols, checkpoints, intelligence gathering, and surveillance. The findings reveal that 89.4% of respondents confirmed active patrol systems, 73.2% acknowledged the use of distress call numbers, and 81.8% affirmed intelligence collection from locals. The study also highlights the strategic collaboration between CWCs and vigilante groups, noted by 93.8% of respondents. Qualitative data further reinforces the interconnectedness of these approaches, revealing that CWCs rely on local informants, surveillance practices, and incentivised intelligence to detect and disrupt criminal activities. The study draws on Broken Windows Theory to explain how visible, community-based crime control mechanisms foster order and deter criminal intrusion. Based on the empirical findings, the study recommends that the Katsina State Government should provide the CWCs with affordable surveillance technologies such as solar-powered CCTV systems, rural reconnaissance drones, and mobile applications for anonymous tip-offs. Simultaneously, community-wide sensitisation programs should be implemented to educate the public on the functions of CWCs and promote active civilian participation in crime reporting and collaborative security efforts.